Oxidative stress-induced C/EBPβ inhibits β-catenin signaling molecule involving in the pathology of preeclampsia. Issue 8 (August 2015) - Zhuang, B.; Luo, X.; Rao, H.; Li, Q.; Shan, N.; Liu, X.; Qi, H.
Abstract Introduction Oxidative stress-induced trophoblast cell dysfunction is a major pathology in preeclampsia (PE). Recently, CCAAT/enhancer binding protein beta (C/EBPβ) has been investigated as a tumor suppressor that participates in tumor invasion. However, the function of C/EBPβ in trophoblast cells remains unknown. Our study was designed to detect the expression of C/EBPβ in the preeclamptic placenta and to identify the underlying mechanisms of oxidative stress. Methods Human placental tissues with PE were collected. The expression of C/EBPβ and β-catenin were detected. Human first trimester extravillous trophoblast cell (HTR8/SVneo) line exposed to hypoxia/reoxygenation (H/R) was employed as an oxidative stress model in vitro to investigate the effects of C/EBPβ on invasion and the expression of β-catenin. Moreover, first trimester-derived placental villous explants were used to verify the effects of C/EBPβ and β-catenin in placentation. Results In preeclamptic placentas, C/EBPβ was overexpressed and β-catenin was decreased. In addition, C/EBPβ was found to have increased expression in H/R-treated HTR8/SVneo cells and villous explants. C/EBPβ knockdown and β-catenin activation could significantly promote the invasion of HTR8/SVneo cells, enhance the outgrowth and migration in villous explants and inhibit the excessive generation of intracellular ROS. These findings might be related to the increased activities of MMP-2/9 and the decreased expression of TIMP-1/2. Meanwhile, C/EBPβ knockdown remarkably increased the expression of β-catenin. Discussion We hypothesize that the oxidative stress-induced overexpression of C/EBPβ might influence the activity of MMPs by regulating the Wnt/β-catenin signaling pathway to affect the invasion of trophoblast cells, which then participate in the pathogenesis of preeclampsia.